The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/lang.12316
|View full text |Cite
|
Sign up to set email alerts
|

First Language Attrition as a Function of Age at Onset of Bilingualism: First Language Attainment of Turkish–English Bilinguals in the United Kingdom

Abstract: This investigation aimed to provide insights into the controversial debate on the role that age at onset of bilingualism plays in human language capacity with a focus on what it entails for first language (L1) attrition. L1 performance of Turkish immigrants (n = 57) in the United Kingdom with age at onset ranging between 7 and 34 years was compared to that of Turkish monolingual controls (n = 29) across two linguistic properties: structural complexity and accent. Findings generally showed that although the imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 82 publications
1
30
0
1
Order By: Relevance
“…Despite a tendency across such Turkish communities to remain loyal to their language and culture and a high level of endogamy (e.g., Backus, ), linguistic changes have been observed in a range of studies. These changes may affect all areas of the language, from accentedness (Karayayla & Schmid, ; Stangen, Kupisch, Proietti Ergün, & Zielke, ) through grammatical (e.g., Gürel, ; Onar Valk & Backus, ; Yağmur, ; Yılmaz, ), morphological (Arslan, De Kok, & Bastiaanse, ; Karayayla, in press; Pfaff, ), and lexical (Backus, ; Karayayla, 2018; Treffers‐Daller, Daller, Furman, & Rothman, ; Yılmaz & Schmid, ) complexity and sophistication.…”
Section: Turkish As An Immigrant Language In Western Countriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite a tendency across such Turkish communities to remain loyal to their language and culture and a high level of endogamy (e.g., Backus, ), linguistic changes have been observed in a range of studies. These changes may affect all areas of the language, from accentedness (Karayayla & Schmid, ; Stangen, Kupisch, Proietti Ergün, & Zielke, ) through grammatical (e.g., Gürel, ; Onar Valk & Backus, ; Yağmur, ; Yılmaz, ), morphological (Arslan, De Kok, & Bastiaanse, ; Karayayla, in press; Pfaff, ), and lexical (Backus, ; Karayayla, 2018; Treffers‐Daller, Daller, Furman, & Rothman, ; Yılmaz & Schmid, ) complexity and sophistication.…”
Section: Turkish As An Immigrant Language In Western Countriesmentioning
confidence: 99%
“…Language Learning 70:S1, March 2020, pp. 54-84 accentedness (Karayayla & Schmid, 2019;Stangen, Kupisch, Proietti Ergün, & Zielke, 2015) through grammatical (e.g., Gürel, 2004;Onar Valk & Backus, 2013;Yagmur, 1997;Yılmaz, 2011), morphological (Arslan, De Kok, & Bastiaanse, 2015;Karayayla, in press;Pfaff, 1993), and lexical (Backus, 2012;Karayayla, 2018;Treffers-Daller, Daller, Furman, & Rothman, 2016;Yılmaz & Schmid, 2012) complexity and sophistication.…”
Section: Turkish As An Immigrant Language In Western Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Accentedness: while monolingual populations are typically perceived to be at ceiling in global foreign accent rating experiments, several studies have established an increase in variance of such ratings in immersed late bilinguals which can lead to some attriters being perceived as unambiguously non-native (e.g., de Leeuw et al, 2010; Hopp and Schmid, 2013; Bergmann et al, 2016; Karayayla, 2018: ch. 4) and subtle shifts occurring in the production of both segmentals and suprasegmentals away from monolingual native norms (e.g., Mennen, 2004; de Leeuw, 2008; Chang, 2012; Bergmann et al, 2016).…”
Section: Problems Of Measurementmentioning
confidence: 99%
“…A wide range of studies have demonstrated this, for example, for complex and infrequent syntactic phenomena. For example, several studies of embedding structures in L1 Turkish have found attriters to diverge most from monolinguals on those types of embedding which are morphologically the most complex (i.e., involve the highest number of suffixations/transformations) and occur least frequently in free speech (e.g., Yagmur, 1997; Yılmaz, 2011; Karayayla, 2018). In a similar vein, attriters are consistently outperformed by non-attrited controls when it comes to the completion of complex written tasks (such as C -tests or cloze tests, e.g., Schmid and Dusseldorp, 2010; Cherciov, 2011; Varga, 2012; Kasparian, 2015).…”
Section: Problems Of Measurementmentioning
confidence: 99%